The Role of Financial Management in Business Sustainability: A Global Systematic Literature Review - Ruki Ambar Arum; Sirna (Pustaka Digital Indonesia, 2026)
In the contemporary business landscape, achieving sustainability has become a strategic imperative, necessitating the integration of financial management practices into corporate decision-making. This study presents a Global Systematic Literature Review examining the role of financial management in promoting business sustainability, synthesizing findings from 95 peer-reviewed articles published between 2021 and 2025. The review identifies key mechanisms through which financial management influences sustainable outcomes, including strategic financial planning, ESG (Environmental, Social, Governance) integration, sustainability reporting, green accounting, and adoption of FinTech innovations. Evidence indicates that effective financial management enhances resource allocation, mitigates risks, and fosters long-term profitability while aligning with social and environmental responsibilities. Furthermore, sustainability reporting and ESG-focused financial strategies are found to increase investor confidence, lower financing costs, and improve firm valuation. Contextual factors such as firm size, industry characteristics, governance structures, and regional regulatory environments were also observed to moderate these relationships. Despite significant advancements, the literature exhibits gaps in cross-industry generalizability, measurement consistency, and integration of behavioral dimensions in financial decision-making. The study contributes to theory by linking Stakeholder Theory, Signaling Theory, and the Resource-Based View to sustainable financial practices. Practically, it provides managerial guidance on embedding ESG criteria, implementing high-quality sustainability reporting, and leveraging digital financial tools to achieve long-term sustainability. The findings underscore the centrality of strategic financial management in bridging corporate strategy and sustainable business performance, offering a comprehensive framework for both scholars and practitioners navigating the evolving global economic landscape